Hydrogen production from absorption-enhanced steam gasification of Enteromorpha prolifera and its char using Ce-doped CaO material. (1st March 2021) - Yan, Xianyao; Li, Yingjie; Sun, Chaoying; Wang, Zeyan
Graphical abstract: Highlights: Enteromorpha prolifera (EP) and its char is used to produce H2 by steam gasification. CeO2 improves H2 concentration and yield from EP and its char using CaO. H2 concentration from EP char using Ce-doped CaO can reach 77.8% after 20 cycles. Mass ratio of CeO2 to CaO = 10:90 in Ce-doped CaO is better for H2 production. Ce-doped CaO maintains stable and porous structure during cycles for H2 production. Abstract: In this work, H2 production performances from Enteromorpha prolifera and its char by absorption-enhanced steam gasification using Ce-doped CaO material were investigated. The Ce-doped CaO material improves the H2 production from Enteromorpha prolifera by steam gasification, which achieves 79.0 vol% H2 in the syngas. The Ce-doped CaO material with the mass ratio of CeO2 /CaO = 10:90 seems more appropriate for high H2 production, tar and char conversion. The presence of CeO2 leads to good cyclic stability in H2 production from Enteromorpha prolifera char during the gasification/calcination cycles. After 20 cycles, H2 concentration and yield from Enteromorpha prolifera char achieve 77.8 vol% and 141.8 mL/g using Ce-doped CaO material, respectively. The CeO2 facilitates the conductivity of electrons in CaO surface due to the existence of Ce 3+ species, thus CO2 capture, water gas shift, and steam methane reforming reactions are promoted by CeO2 . The Ce-doped CaO material maintains the porous microstructure and fine particles during the cycles due to the support of CeO2 . Therefore, H2 productions from Enteromorpha prolifera and its char by absorption-enhanced steam gasification using Ce-doped CaO material appear promising.